Combination therapy using advanced biomaterials in the management of mandibular Grade II furcation defect - Paladugu Devi Navya; Arvina Rajasekar (Wolters Kluwer Medknow Publications, 2022)
Periodontitis is a multifactorial disease. Even though plaque is a primary etiological factor; there are so many aggravating factors such as calculus, genetics, lifestyle habits, systemic health, and occlusal trauma. Trauma from occlusion is caused by occlusal force that surpasses the periodontium's adaptive capacity, causing injury to periodontal structures. This case highlights the management of a furcation defect of Grade II which was induced by occlusal trauma. The patient presented with periodontal abscess in relation to 36 and on radiographic examination, bone loss and high points were evident in relation to endodontically treated 36. A full-thickness mucoperiosteal flap was elevated and after debridement injectable platelet-rich fibrin (iPRF), osseograft, and guided tissue regeneration (GTR) membrane were placed. The patient was recalled after 3 months for re-evaluation. On re-evaluation, the radiograph showed adequate bone fill which suggested that using iPRF, bone graft, and GTR may enhance periodontal regeneration in Grade II furcation defects. Therapy using iPRF, bone graft, and GTR may enhance in Grade II furcation problems, and periodontal regeneration is possible.